Возможности акустического прогнозирования гранулометрии частиц при струйном измельчении - Горобец, Л. Ж.; Прядко, Н. С.; Левченко, К. А.; Машкова, Т. Ю.; Верхоробина, И. В. (НТУ "ХПИ", 2014)
Приведены результаты исследования связей гранулометрического состава измельченных частиц с тех-нологическими и акустическими показателями струйной мельницы. Показана возможность прогнози-рования среднего размера частиц по максимальной амплитуде акустических сигналов при транспорти-ровании или струйном измельчении.

Research results of connections size structure of the crushed particles with amplitude size and acoustic signals distributions in transportation zones and jet mill grinding are resulted. It is established, that displacement of a distribution maximum in a range of amplitude smaller values specifies effect of accumulation in jet particles of the small sizes. The opportunity of medium-sized particle forecasting on the maximal amplitude of acoustic signals is shown at transportation or jet grinding. On a basis of fore-casting estimations it is possible a control and managements of particle size structure by realization of acoustic monitoring of jet grinding process.
Acoustic forecasting opportunities of particle size testing at jet grinding
Keywords: метод акустической эмиссии; акустические сигналы; технологические показатели; струйная мельница; акустические параметры; grinding; granulometry; technological index; acoustic parameter